PERBANDINGAN BESAR GAYA GESER ANTARA EMPAT UKURAN PANJANG LENGAN AKTIF FINGER SPRING - , VINA MAWADDAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Finger spring is an active component of orthodontic appliance that is used to move the teeth towards mesial and distal which has the active arm length about 12-15 mm. The force required for tipping movement of the anterior teeth is about 30-50 gr. The purpose of this study is to compare the shear forces between four diffrerent length of finger spring active arms and find out the optimal length of finger spring active arm for tooth movement. This study is an experimental research laboratory. Research subjects were finger spring made from stainless steel 0,6 mm in diameter wire and 0,3 mm of internal diameter coil, the active arm length were 10 mm, 12 mm, 14 mm, and 16 mm respectively 15 pieces. The instument used to measure the shear force was tension gauge with 28.50 of accuracy. Results of shear force measurements were analyzed using the comparative test Kruskal-Wallis and Mann-Whitney. The results showed that the active arm length of 10 mm has the largest shear force, while the active arm length of 16 mm has the smallest shear forces, and the length of the active arm that can provide the optimal force is equal to 16 mm with mean shear force was 39.690 grams. The conclusion of this study is that there is a big difference in shear force between the four active arm length finger spring, the longer the length of the active arm finger spring, the force generated is getting smaller, and length of finger spring active arm for optimal tooth movement that is equal to 16 mm. Key word : finger spring. shear force, tooth movement